Oakbank Dog Rose: A Working-model of an Iron Age Wooden Whistle from a Loch Tay Crannog - Simon Wyatt (EXARC, 2021)
In 1980 a small piece of worked wood was discovered during excavation at Oakbank crannog in Loch Tay, Scotland. It was interpreted as a whistle by Nick Dixon. While there are several other Iron Age artefacts which have been interpreted as whistles, in Britain, this is the only one currently known to the author which is made of wood. This paper describes the manufacture and sounding of a model of this Iron Age artefact in order to explore its sonic range and establish whether it may be classified as a whistle.